2020
DOI: 10.3390/brainsci10080477
|View full text |Cite
|
Sign up to set email alerts
|

Pain Processing in Older Adults and Its Association with Prefrontal Characteristics

Abstract: Aging is known to affect nociceptive processing, e.g., the ability to inhibit pain. This study aims to investigate whether pain responses in older individuals are associated with prefrontal characteristics, namely (i) executive functioning performance and (ii) structural brain variations in the prefrontal cortex. Heat and pressure stimuli were applied to assess pressure pain sensitivity and endogenous pain inhibition in 46 healthy older individuals. Executive functioning performance was assessed in three domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Two studies that examined white matter integrity—a major correlate of EF [ 15 ]—in relation to self-reported pain in normal and pathological cognitive aging found that reduced white matter integrity (presumably reflecting worse EF) was related to higher self-reported, clinical pain levels [ 16 , 17 ]. These studies, therefore, corroborate experimental pain studies, in which worse EF was related to higher pain sensitivity [ 18 , 19 ]; these findings also support the results found in patients with VaD in whom higher pain reports and deficits in EF are concurrently present [ 8 ]. However, there are no studies that explored the roles of EF and white matter concurrently in self-reported, clinical pain in patients with cognitive impairment.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Two studies that examined white matter integrity—a major correlate of EF [ 15 ]—in relation to self-reported pain in normal and pathological cognitive aging found that reduced white matter integrity (presumably reflecting worse EF) was related to higher self-reported, clinical pain levels [ 16 , 17 ]. These studies, therefore, corroborate experimental pain studies, in which worse EF was related to higher pain sensitivity [ 18 , 19 ]; these findings also support the results found in patients with VaD in whom higher pain reports and deficits in EF are concurrently present [ 8 ]. However, there are no studies that explored the roles of EF and white matter concurrently in self-reported, clinical pain in patients with cognitive impairment.…”
Section: Introductionsupporting
confidence: 86%
“…For instance, one study showed that cognitive inhibition explained 20% of the pain response variance in an experimental pain paradigm in pain-free older individuals. In fact, this study showed that a decreased cognitive inhibition and shifting ability were related to higher facial responses due to pressure pain [ 19 ]. This could reflect the involvement of EF in endogenous pain inhibition [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the association between pain responses and executive functions in individuals with cognitive impairments (MCI and dementia) has appeared to be robust; there is some variability with regard to which subcategory of executive functioning plays the most important role. Abstract thinking, making plausibility judgments [10], cognitive inhibition, shifting [19], as well as cognitive flexibility (the present study) have been suggested as most important predictors for pain responses in MCI and dementia. Thus, a taxonomy is needed to differentiate between those executive functions that influence pain response and those not sharing this functional property.…”
Section: Discussionmentioning
confidence: 62%
“…Under this perspective, variations in neurocognitive functioning are always linked to variations in pain processing, even at nonpathological levels. There are several studies, which have tried to investigate this by using cross-sectional designs and correlated executive functioning and pain responses in cognitively healthy individuals [11,12,[16][17][18][19]. Using such designs, most studies (approximately 80%) did not find significant associations between the two functions [12].…”
Section: Introductionmentioning
confidence: 99%